Effects of different amendments on the quality of burnt eucalypt forest soils – A strategy for ecosystem rehabilitation. (15th October 2022) - Machado, Ana; Serpa, Dalila; Santos, Ana Karolina; Gomes, Ana Paula; Keizer, Jan Jacob; Oliveira, Bruna R.F.
Abstract: The magnitude of forest fires' impacts on the environment is directly related to the changes induced on soil physical, chemical and biological properties. Using available organic resources to rehabilitate burnt forest soils can help reduce post-fire soil fertility loss, accelerating ecosystem recovery. In the present study, the potential of four soil amendments: a mycotechnosol, a eucalypt residue mulch, dredged sediments from a freshwater lagoon and an organic-mineral biofertilizer, to improve the quality of burnt forest soils in terms of organic matter, carbon, nitrogen and phosphorus contents, was evaluated. Two experiments were set-up, one in a recently burnt eucalypt plantation and another in the laboratory using soils from the same area, to assess the effects of the amendments on soil quality, with both experiments lasting for 7 months. The effects of the amendments on nutrient leaching along the soil profile were also evaluated in the laboratory, to investigate possible negative impacts on groundwater and surface water quality. All amendments increased the organic matter and nutrient contents of burnt soils, confirming their potential for ecosystem rehabilitation. The biofertilizer, however, was found to promote nutrient losses by leaching, largely owing to its high solubility, increasing the risk of contamination of ground and surface waters. Using available organic resources to rehabilitate burnt forests as was done in the present work complies with the idea of a circular economy, being key for the sustainability of forest ecosystems. Highlights: The suitability of different amendments for rehabilitating burnt soils was assessed. Bioamendments boosted organic matter breakdown and increased nutrient availability. Fast degrading amendments favored nutrient leaching, compromising water resources. Using available organic resources is key for the forestry sector sustainability.